2010
DOI: 10.1021/cm102373k
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of P3HT−A Systematic Study of Environmental Factors

Abstract: The influence of environmental factors on the degradation process of P3HT film has been investigated quantitatively. The decay kinetics of the polymer absorption during variation of intensity and spectral distribution of the incident light, oxygen concentration, humidity level as well as temperature are monitored using infrared and UV/vis absorption spectroscopy. Additionally, the oxygen diffusion into the polymer film has been investigated using fluorescence spectroscopy under the same experimental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
258
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(272 citation statements)
references
References 36 publications
9
258
3
2
Order By: Relevance
“…Such an influence of the microstructure was also reported upon photooxidation experiments [24]. Changing the structure of the polymer from regioregular to regiorandom was shown to significantly increase the photooxidation rate by a factor 5 [24].…”
Section: Figurementioning
confidence: 55%
See 3 more Smart Citations
“…Such an influence of the microstructure was also reported upon photooxidation experiments [24]. Changing the structure of the polymer from regioregular to regiorandom was shown to significantly increase the photooxidation rate by a factor 5 [24].…”
Section: Figurementioning
confidence: 55%
“…Changing the structure of the polymer from regioregular to regiorandom was shown to significantly increase the photooxidation rate by a factor 5 [24]. Concerning BA02, AL02 and RE, we showed that the photooxidation rate of RE is the double of BA02 and AL02…”
Section: Figurementioning
confidence: 77%
See 2 more Smart Citations
“…Photodegradation of P3HT in thin fi lms has indeed been well studied. [ 47,48 ] Photobleaching has been observed with an additional blueshift of the absorption associated to an ozone mediated decrease of the average length of π-conjugation. [ 49 ] In solution, on the other hand, the blueshift is not necessarily caused by ozone, but simple UV irradiation in an oxygen containing atmosphere is already suffi cient.…”
Section: Doi: 101002/adma201505521mentioning
confidence: 99%